2019
DOI: 10.1002/ardp.201800310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐(2‐oxo‐2H‐chromen‐4‐yl)acetamides as potent acetylcholinesterase inhibitors and molecular insights into binding interactions

Abstract: Sixteen novel coumarin-based compounds are reported as potent acetylcholinesterase (AChE) inhibitors. The most active compound in this series, 5a (IC 50 0.04 ± 0.01 µM), noncompetitively inhibited AChE with a higher potency than tacrine and galantamine.Compounds 5d, 5j, and 5 m showed a moderate antilipid peroxidation activity. The compounds showed cytotoxicity in the same range as the standard drugs in HEK-293 cells. Molecular docking demonstrated that 5a acted as a dual binding site inhibitor. The coumarin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The dual binding site design reported in this study started from the coumarin motif, which constitutes a privileged and versatile scaffold for bioactive compounds, [14][15][16][17] in particular for the assembly of inhibitors of AChE, where coumarins are known to bind to the peripheral site mainly by π-π interactions. [18][19][20][21][22][23][24][25][26][27] To discover further bases capable of efficient dephosphylation, we replaced the imidazole or pyridine functional groups of reported nonoxime reactivators with nonaromatic primary or secondary amines, which we attached through alkoxy-linkers of various lengths at position 6 and 7 of the coumarin ring system. The resulting primary amines 1-6 (Table 1) contained a linear, amino acid-like substructure, whereas the secondary amines in compounds 7-11 were mostly cyclic, that is, derived from piperidine or pyrrolidine.…”
Section: Resultsmentioning
confidence: 99%
“…The dual binding site design reported in this study started from the coumarin motif, which constitutes a privileged and versatile scaffold for bioactive compounds, [14][15][16][17] in particular for the assembly of inhibitors of AChE, where coumarins are known to bind to the peripheral site mainly by π-π interactions. [18][19][20][21][22][23][24][25][26][27] To discover further bases capable of efficient dephosphylation, we replaced the imidazole or pyridine functional groups of reported nonoxime reactivators with nonaromatic primary or secondary amines, which we attached through alkoxy-linkers of various lengths at position 6 and 7 of the coumarin ring system. The resulting primary amines 1-6 (Table 1) contained a linear, amino acid-like substructure, whereas the secondary amines in compounds 7-11 were mostly cyclic, that is, derived from piperidine or pyrrolidine.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the number of H-bond acceptors ranges from 2-5 for synthesized compounds that are less than 10, and the number of H-bond donors for all synthesized compounds is 2 and thus, less than 5 as per the rule. According to the Lipinski (Pfizer's rule) of five for any chemical compound, as an oral drug would be biologically active if it does not violate more than one rule out of the proposed rules wherein, the first rule said, the octanol-water partition coefficient (milogP) must be ≤5; the second rule said, the molecular weight of the probable drug must be <500 Daltons; the third rule said, taking into consideration of the number of H-bond acceptors in the molecule under consideration must be ≤10 and the last rule said, the number of H-bond donors must be ≤5 [32,33]. Table 9 disclosed bioactivity results, showing that the parameters of all the synthesized compounds were within limits of Lipinski's rule of five with no violation of rules.…”
Section: Drug Likeness (Molinspiration Physicochemical Parameters)mentioning
confidence: 99%
“…Recent studies showed that activity of BuChE in the brain of AD patients with the progression of the AD increased while AChE activity in these patients declines. Therefore, inhibition of both types of ACh degrading enzymes may be beneficial in AD treatment …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, inhibition of both types of ACh degrading enzymes may be beneficial in AD treatment. [7] The phthalimide is a bicyclic heterocyclic scaffold and its derivatives have diverse range of biologically activities such as anti-inflammatory, anticonvulsant, hypolipidemic, analgesic, and immunomodulatory activities. [8 -13] Recently, several derivatives of phthalimide with high inhibitory activity against AChE have been reported ( Figure 1A and B).…”
Section: Introductionmentioning
confidence: 99%